Pairing, Their Own Aspects and Corresponding Methods of Work with Pairing in the Autocad Software - Ismonov Khurshidbek Bakhtiyorovich; Abdujalolov Sardorbek Abdujalol ogli; Ruziyev Nuriddin Mukhammadaliyevich; Abduraimova Muazzamoy Abdukodir qizi (International Journal on Orange Technologies, 2021)
The article reveals the specifics of establishing connections in drawing lessons, which is one of the most pressing issues of modern pedagogy, as well as the introduction of innovative technologies into computer programs. The purpose of the work is the role of connections in the development of equipment that we encounter in our lives, and their implementation using graphics software. The drawing broadly shows the execution of fillets and their processing in AutoCAD.